LINGKUNGAN KELUARGA DAN PRAKTIK KERJA INDUSTRI SERTA MOTIVASI KERJA SISWA KELAS XII SMK NEGERI 1 TONDANO - Bunga Koerynia Wahti, Louisa N. Kandoli, Metsi Daud (Program Studi Pendidikan Teknologi Informasi dan Komunikasi, Universitas Negeri Manado, 2021)
This research was conducted at SMK Negeri 1 Tondano. The purpose of this study was to obtain empirical results of direct and indirect effects on family environment variables (X1) and industrial work practices (X2) as independent variables, and work motivation (Y) as dependent variables. This research includes quantitative research. The research sample was 85 students. Data collection techniques using a questionnaire (questionnaire). The analysis technique used is normality test, linearity test and regression coefficient significance test. The results showed the normality test, namely the family environment variable Sig value = 0.159 > 0.005, the industrial work practice variable Sig value. = 0.156 < 0.05, and the work motivation variable Sig. = 0.275 > 0.05. The linearity test of work motivation (Y) on the family environment (X1) is 0.861 > 0.05, and shows the calculated F value = 0.567 < Ftable (0.05.12/71) = 1.89, which means it is significant and the relationship between the two data has a linear pattern. And work motivation (Y) on industrial work practices (X2) 0.862 > 0.05, and shows the calculated F value = 0.630 < Ftable (0.05.18/65) = 1.764, which means that the data is significant and the relationship is linear. The results of the significance test of the regression coefficient of the relationship between family environment (X1) and work motivation (Y) were 0.650 (r2 = 0.422 = 42%). industrial work practices (X2) and work motivation (Y) of 0.811 (r2 = 0.774. = 77 %). Variable family environment, industrial work practices simultaneously with work motivation contributed to the value of R = 0.869 and the coefficient of determination (RSquare) of 0.755 = 75 %.